Hubungan Skor Plasenta Akreta Indeks (PAI) dengan Kejadian Plasenta Akreta pada pasien bersalin di bagian kebidanan RSUP.dr.M.Djamil Padang - Intan Firmana Putri; Ariadi Ariadi (Universitas Andalas, 2019)
Objective: To determine the relationship between PAI scores and the incidence of placenta accreta in placenta previa accreta suspects who gave birth at RSUP M. Djamil Padang. Method: This study is an analytical study using a cross-sectional study design with a sample of all patients with placenta previa totalis suspected accreta who gave birth in the obstetrics department of RSUP M. Djamil Padang during the period January 1, 2017 - April 30, 2018. The data were taken from the patient's medical records that included age, parity status, labor history, and PAI score from ultrasound examination results. The relationship between PAI scores and the incidence of placenta accreta was analyzed using an independent T-test with a significant degree of <0.05. The research results are presented in tabular form. Results: During the study period, 30 patients with placenta previa suspected of accreta at RSUP M. Djamil Padang. It is known that cases of placenta accreta were more common in multiparous (57.7%), suspected accreta (57.7%), had a history of SC (65.2%), and the mean age of patients with accreta was 34.7 ± 3.5 years. Furthermore, it can be concluded that the mean PAI score in patients with placenta accreta is higher than non-accreta, and there is a significant relationship between PAI scores and cases of placenta accreta (p> 0.05).Conclusion: The mean PAI score in patients with placenta accreta is higher than without accreta and there is a significant relationship between PAI scores and cases of placenta accreta.Keywords: Placenta Accreta, PAI Score